PEMANFAATAN E-MAIL DALAM KORESPONDENSI SEBAGAI PERWUJUDAN PAPERLESS OFFICE DI PT TELKOM - ROZALIN K, STEVANI (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2013)
ABSTRACT Utilization of e-mail in correspondence can realize the paperless office. It is known by reducing paper use after utilization of e-mail in the correspondence. This research is a qualitative descriptive study. Informants in this study was the secretary of the Executive General Manager (EGM) and the Executive Deputy General Manager (DEGM) and 14 informants as employees of Divisi Telkom Timur. In this research, collection data techniques are in-depth interviews, observation, documentation and questionnaires. Analyzed using taxonomy and percentage on the questionnaire. The results showed that PT Telkom has implemented the utilization of e-mail in the internal and external correspondence as the embodiment of a paperless office by Nota Dinas Elektronik and Mail which contained in the internal portal PT Telkom. This is supported by the responses of 14 employees who have understand and use e-mail and also contribute to realization of the paperless office.    Keywords : utilization of e-mail, correspondence, paperless office